2015
DOI: 10.1051/matecconf/20152702008
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of Polyacrylonitrile-Kapok Hollow Microtubes Decorated with Cu Nanoparticles

Abstract: Abstract.A novel copper (Cu) nanoparticle carrier was fabricated using kapok natural microtubes as a substrate. Cu nanoparticles were grown on a thin polymer film on the surface of the kapok fibers. The polymer film was deposited on the surface of the microtube using a surfactant-assisted polymerization of acrylonitrile monomers. Cetyltrimethyl ammonium bromide (CTAB) was used surfactant. The contact angle decreased from 120.5 to 0 after polyacrylonitrile coating (PAN), which suggests improved hydrophilicity o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…The kapok fibers kept their porous form in all CTAB doses tested, indicating that the top kapok layer area was not reduced. These findings definitely suggest that CTAB has a substantial role in distributing PAN atoms throughout the kapok fiber top layer [106].…”
Section: Coated Of Kapok Fibermentioning
confidence: 62%
See 1 more Smart Citation
“…The kapok fibers kept their porous form in all CTAB doses tested, indicating that the top kapok layer area was not reduced. These findings definitely suggest that CTAB has a substantial role in distributing PAN atoms throughout the kapok fiber top layer [106].…”
Section: Coated Of Kapok Fibermentioning
confidence: 62%
“…The kapok fibers kept their porous form in all CTAB doses tested, indicating that the top kapok layer area was not reduced. These findings definitely suggest that CTAB has a substantial role in distributing PAN atoms throughout the kapok fiber top layer [106]. Although raw fiber is compared to surface-coated fiber, the rough surface with low surface energy efficiently prevents oil from flowing from the fiber structure, leading to a high oil sorption rate.…”
Section: Coated Of Kapok Fibermentioning
confidence: 90%
“…Agcaoili et al. have found that by coating kapok microtubes with polyacrylonitrile, high adsorption capacities for methylorange (34.72 mg g −1 ) and copper (90.09 mg g −1 ) can be achieved . With a proper functionalization, kapok fiber can show excellent properties for the removal of heavy metal ions like copper from aqueous solution.…”
Section: Functionalizing Cellulosementioning
confidence: 99%